People of mountains: An ethnographic study of the effects of emigration on left-behind population in the rural of Azerbaijan - Gurbanaliyeva,Ayshan (2022)
Migration is a globally studied social issue, that can cause changes in the demographic composition of the population and the structure of society. Azerbaijan has been experiencing different waves of migration in the country since gaining its independence. One of the largest waves is the emigration from rural to urban areas. Although there are studies focusing on why people leave the villages, there is a lack of information regarding the populations left behind in the rural areas. This study aims at understanding how people left behind manage to maintain their lives, experiencing an increasing depopulation. The analysis is made based on the data obtained from the ethnographic fieldwork conducted in one of the villages in Azerbaijan. The thesis tries to reveal the role of migration in the lives of the villages and to show its effects on different groups in the community such as women, elderlies, children, men, and families.
Keywords: social anthropology; rural-urban migration; left-behind; social continuity; migration ideology